Tropical phytotherapeutic treatment for achieving knee symmetry in osteoarthritis – A sustainable approach - Apurba Ganguly (International Journal of Phytomedicine, 2014)
Throughout the world a large number of patients suffering from osteoarthritis are undergoing knee surgery and knee replacement every year. Though the surgery or replacement methods are expensive , these cannot make both knees symmetrical in all anatomical measurements.The present paper , reports for the first time , a noble method ,alternative to knee surgery by topical applications of phytoconstituents.The treatment involves topical applications of phytoconstituents from medicinal plants by manually applied with wooden roller and pluse-therapy technique for a period of 42days. The patients recover completely from osteoarthritis pain and both their knees become symmetrical anatomically , supported by pathological and radiological observations.